Probing the Dynamics of Spontaneous Quantum Vortices in Polariton Superfluids - Liew, Timothy Chi Hin (2017)
The experimental investigation of spontaneously created vortices is of utmost importance for the understanding of quantum phase transitions towards a superfluid phase, especially for two-dimensional systems that are expected to be governed by the Berezinski-Kosterlitz-Thouless physics. By means of time-resolved near-field interferometry we track the path of such vortices, created at random locations in an exciton-polariton condensate under pulsed nonresonant excitation, to their final pinning positions imposed by the stationary disorder. We formulate a theoretical model that successfully reproduces the experimental observations.